Fracture resistance of endodontically treated permanent anterior teeth restored with three different esthetic post systems: An in vitro study - Ameet J Kurthukoti; Jaya Paul; Kapil Gandhi; Divya B J Rao (Wolters Kluwer Medknow Publications, 2015)
Background: Esthetic coronal reconstruction of fractured anterior teeth is often performed using intra radicular posts. Most of the commonly used commercially esthetic post systems do not exhibit similar physical properties as dentin resulting in failures. Aim: To evaluate and compare the fracture resistance and mode of failure of simulated traumatized permanent central incisors restored with three different post systems including biologic dentin posts. Materials and Methods: A total of 40 recently extracted human maxillary central incisors with similar dimensions were decoronated 2 mm above the cemento-enamel junction and endodontically treated. Ten specimens were randomly selected as the Group I - Control group (core built teeth without intraradicular posts). The remaining 30 teeth were equally divided and restored with zirconia (Group II, n = 10), fiber re-inforced composite (FRC) (Group III, n = 10) and biologic dentin posts (Group IV, n = 10) using resin bonded cement and their cores built-up. These samples were embedded in acrylic resin and then secured in a Universal Testing Machine and subjected to fracture resistance testing. The location of failure in the specimens was evaluated using a stereomicroscope. Results: Intergroup comparison revealed that the control group and zirconia post group (522 ± 110 N) demonstrated the least fracture resistance, while dentin post group (721 ± 127 N) the highest. There was no statistically significant difference between fiber post and dentin post groups. Fractures that were repairable were observed in fiber post and dentin post groups, whereas mostly unrestorable, catastrophic fractures were observed in the zirconia post group. Conclusion: Teeth restored with the biologic dentin post system demonstrated the highest fracture resistance and repairable fractures, closely followed by FRC post system. The least fracture resistance and most catastrophic fractures were demonstrated by the zirconia post system.